Análise do atendimento aos princípios da certificação de manejo florestal FSC e perspectivas de aplicação dos Indicadores Genéricos Internacionais - Bonfim, Mayra de Souza (2016)
In recent decades, the intensification of environmental concern generated by human activities is causing reflexes in various sectors of society. In this context the market started to demand information and guarantees about the forest products. One of the tools developed for this purpose is the forest certification, represented in Brazil mainly by the Forest Stewardship Council (FSC). In addition to attest the management system, the forest certification requires compliance with the laws in force in the country and of social, economic and environmental more restrictive criteria. For certification and maintenance of the certificate, it is required that all non-compliances with requirements of the standards are treated in the sense of being corrected by avoiding their recurrence. Thus, this study aims to analyze the future changes arising from the integration of International Generic Indicators (IGIs), taking into account the difficulties encountered for compliance with the current standard in the process of FSC certification audits in the context of forest plantations in Brazil. To this end, were obtained data and information from forest management certification audits in the last five years. The results obtained indicate that organizations have a higher difficulty to meet the Principles 4, 6, 7 and 8, strictly linked to the social aspects, such worker’s rights and community relations, environmental impacts, and social and environmental monitoring. The changes arising from the IGIs are mainly related to the new concepts and approaches that impact directly in social areas, environmental impact assessment/monitoring, and management of the forest management. Analyses intend to contribute and support decision-making by the forest sector, and assist in the process of recertification and certification processes of new organizations